Cars and clothes in South Africa's Covid experience: The contrasting fortunes of two manufacturing sectors in South Africa - Ben Scully; Wellington Mvundura; Tessa Nyirenda; Bukiwe Tambulu; Usithandile Zikalala (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
This paper uses the automobile industry and the clothing and textile industry as lenses to examine the impact of the Covid pandemic on globalization. We focus on the case of South Africa, where both sectors have a long history. In the early decades of neoliberal globalization the country's clothing and textile industry declined rapidly and the automobile industry expanded dramatically. The Covid crisis has had an overall negative effect on the economy of South Africa, but in certain respects the trends of these two key manufacturing sectors have reversed. The Automobile sector in the country is stagnating and both firms and government seem unable to take significant action to address the situation. The clothing and textiles industry has stabilized, and even begun to grow, after decades of decline from the 1980s to the 2000s. The pandemic period has seen renewed energy and engagement between firms and government. We analyze the background and Covid experiences of both industries to make sense of the explanation for and implications of this contrast.
Keywords: L16; L52; O55; 330; Covid-19; South Africa; Globalization; Automobile Industry; Clothing and Textile Industry